Antimicrobial Peptides as an Alternative for the Eradication of Bacterial Biofilms of Multi-Drug Resistant Bacteria - de Pontes, Janaína Teixeira Costa [UNESP]; Borges, Anna Beatriz Toledo [UNESP]; Roque-Borda, Cesar Augusto [UNESP]; Pavan, Fernando Rogério [UNESP] (MDPI, 2022)
Bacterial resistance is an emergency public health problem worldwide, compounded by the ability of bacteria to form biofilms, mainly in seriously ill hospitalized patients. The World Health Organization has published a list of priority bacteria that should be studied and, in turn, has encouraged the development of new drugs. Herein, we explain the importance of studying new molecules such as antimicrobial peptides (AMPs) with potential against multi-drug resistant (MDR) and extensively drug-resistant (XDR) bacteria and focus on the inhibition of biofilm formation. This review describes the main causes of antimicrobial resistance and biofilm formation, as well as the main and potential AMP applications against these bacteria. Our results suggest that the new biomacromolecules to be discovered and studied should focus on this group of dangerous and highly infectious bacteria. Alternative molecules such as AMPs could contribute to eradicating biofilm proliferation by MDR/XDR bacteria; this is a challenging undertaking with promising prospects.
Keywords: antimicrobial peptides; antimicrobial resistance; biofilm; drug discovery; extensive drug resistance; MDR bacteria